(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2012)
In this paper differential attack on S-DES is carried out. S-DES is the reduced version of DES algorithm. This algorithm operates on 8-bit message block with 10-bit key and DES operates on 64-bit message block with 56-bit key. This paper analyzed the differential attack on S-DES. Differential attack is used to break a cipher by trying each possible key.